Safety and efficacy of a feed additive consisting of Sepiolitic clay for all animal species (Mineria y Tecnologia de Arcillas SA ‐ MYTA). (15th June 2022) - ,; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the re‐evaluation of the authorisation of Sepiolitic clay as a feed additive for all animal species. The FEEDAP Panel considered that Sepiolitic clay is unlikely to be absorbed. Harmful amounts of residues of any chemical component in edible tissues/products, as a consequence of the use of Sepiolitic clay as a feed additive, are not expected. Sepiolitic clay is not genotoxic and does not induce any toxicity effects following oral administration and, therefore, it was considered safe for the consumers. Based on the data available, the FEEDAP Panel concluded that Sepiolitic clay is safe for dairy cows and weaned piglets at 20, 000 mg/kg feed. These conclusions were extrapolated to other dairy ruminants, pigs for fattening and other growing Suidae . The additive is considered safe for chickens for fattening at 10, 000 mg/kg feed and for salmonids at 17, 600 mg/kg feed. Considering that it is not possible to establish a comparable margin of safety in the four major species, the Panel cannot conclude on the safety of Sepiolitic clay for other animal species/categories. Owing to the dusting potential of the additive and its crystalline silica content, handling the additive is considered a risk by inhalation for the users. It is not irritant or corrosive to skin or eyes. Due to the nickel content, it is considered a skin and respiratory sensitiser. The additive is considered safe for the environment. The FEEDAP Panel concluded that Sepiolitic clay is efficacious as binder and anticaking agent in feed for all animal species under the proposed conditions of use.